Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory

Illustration of paradigm pluralism in computing education research - Thota, Neena; Berglund, Anders; Clear, Tony (Conferences in Research and Practice in Information Technology Series, 2012)
This paper argues for paradigm pluralism in computing education research. The value of mixing paradigms, and the choice of methodological eclecticism and mixed methods is explored using pragmatic knowledge claims. A research study, which focused on the design of an introductory object-oriented programming (OOP) course for undergraduate students, is introduced as an illustration of paradigm pluralism. The study demonstrates methodological eclecticism and use of mixed methods for data collection and analysis. Meaningful outcomes resulting from the choice of the research design are described. A framework that focuses on the research problem and research questions to guide research design is presented as the outcome of the study. Through the discussion and demonstration of paradigm pluralism, this paper contributes to increased awareness of theoretically anchored research in computer science. © 2012, Australian Computer Society, Inc.
Publisher: ACS

A Glimpse into the Cultural Situatedness of Computer Science: Some Insights from a Pilot Study - Berglund, Anders; Thota, Neena (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
To what extent is students' understanding of computer science culturally situated? This, possibly philosophical question, has come to the surface at Uppsala University, Uppsala, Sweden, where many Chinese students study computer science together with the local students. We did an exploratory study using email interviews to see if our intuitions could be relied on. We collected data from Chinese students studying in master programs and analysed the data using a phenomenographic perspective. A complex intertwined relationship between the content of their learning (the WHAT), the ways in which they went about studying (the HOW), the aims of their studies (the WHY), and the competencies developed from the intercultural context they studied in (the WHERE) was observed. In this paper we offer some insights from the results of the pilot study and discuss how they have shaped our on-going study in the field.
Keywords: Computer science; Context; Cultural differences; Educational institutions; Global communication; Interviews; computer science education; cultural context